The impact of Virtual communities on political systems (قضايا سياسية, 2024)
The rapid development in communications and means of communication has led to the emergence of new communities that have had a significant impact on the domestic and foreign policies of countries. Therefore, it has become necessary to study these communities and their influence on political systems. These communities have become key tools in shaping public opinion and a platform for freely expressing opinions. We can say that virtual communities have become a broader arena for practicing democracy than ever before, and they have both positive and negative impacts on political participation. Thus through this research we will attempt to shed light on these communities and how they affect political system.